Professional construction management : including C.M., design-construct, and general contracting - Barrie, Donald S.; Paulson, Bouyd C. (New York : McGraw-Hill, 1992)
This book is divided into four parts: Construction industry and practice; Professional construction management in practice; Methods in project management; and Business methods in managing construction.
Includes index.
Keywords: Management; Construction industry; Construction industry -- Management; Value analysis (Cost control)